Avifauna en dos parches de bosque seco del departamento del Valle Cauca, Colombia (2014)
In a study conducted between the months of July and December of 2012, two patches of tropical dry forest from the geographic valley of the Cauca river (Colindres-Jamundi and Las Chatas-Buga) were followed. To collect the data, point counts and transects were used; additionally mist nets were used for the recognition of small and inconspicuous birds. 2364 birds, corresponding to 1462 records, divided into 76 species, 27 families and 16 orders were observed. The family with the greatest number of species was Tyrannidae (14), followed by Thraupidae (seven), then Ardeidae (five) and Picidae (five). In the Chatas Forest 51 species, grouped among 20 families were found, while in the Colindres Forest 59 species, grouped among 25 families were found. The data presented, contributes to the knowledge regarding the actual diversity of the bird population that still exists in two of the few patches of tropical dry forest remaining in the geographic valley of the Cauca river, and its relationship with the size and type of matrix surrounding these patches. These data could be taken into account for the design of management and conservation strategies of the dry forest, to mitigate the damage done by the monoculture of sugarcane and human intervention in general, responsible for its high vulnerability.